Optimizing the Placement of Integration Points in Multi-hop Wireless Networks - Chandra, Ranveer; Qiu, Lili; Jain, Kamal; Mahdian, Mohammad (IEEE International Conference on Network Protocols (ICNP), 2004)
Efficient integration of a multi-hop wireless network with the Internet is an important research problem. In a wireless neighborhood network, a few Internet Transit Access Points (ITAPs), serving as gateways to the Internet, are deployed across the neighborhood; houses are equipped with low-cost antennas, and form a multi-hop wireless network among themselves to cooperatively route traffic to the Internet through the ITAPs. For both these applications, placement of integration points between the wireless and wired network is a critical determinant of system performance and resource usage. In this paper, we explore the placement problem under three wireless link models. For each link model, we develop algorithms to make informed placement decisions based on neighborhood layouts, user demands, and wireless link characteristics.We also extend our algorithms to provide fault tolerance and handle significant workload variation. We evaluate our placement algorithms and show that our algorithms yield close to optimal solutions over a wide range of scenarios we have considered.